L’enseignement supérieur en Angola face aux inégalités : influences françaises dans les trajectoires politiques - Isabelle de Geuser; Benoît Josset (Éducation et Socialisation)
Angola is in the wake of a tough historical past under war during which the higher education system was almost nonexistent. Since 2002, year of the peace accord signature, this system is structuring and on mutation. In 2009, the arrival of a higher education politics became a leitmotif for answering socioeconomic inequality. Extension (decentralization), internationalization (student mobility) and privatization (rising of a private higher education) characterize the measure took by the government over the last ten years. Through an exploratory research of the mutation of Angola higher education system, we will showcase the political trajectories in Angola in the field of higher education through the influence of the French diplomacy.